Factors influencing intergenerational succession in family farm businesses in Brazil. (September 2019) - Pessotto, Ana Paula; Costa, Carlos; Schwinghamer, Timothy; Colle, Gabriel; Corte, Vitor Francisco Dalla
Highlights: Parental encouragement increases the probability of potential successors to remain in the family farm business. Family farm income & succession planning increase the odds of having a successor. Farm mechanization level increases the odds of a potential successor wishing to remain. Abstract: Increasing life expectancy and family farm business succession are affecting rural societies and economies in Brazil. There were hypothesized to be a large number of factors influencing family farm business succession, and the hypothesized factors were quantified based on survey results from 213 owners and 176 potential successors of family farm businesses in Rio Grande do Sul State (Brazil). The concept of successor identification was indicated by Bernoulli/binary responses to whether or not potential successors wished to remain of the family farm and whether or not the successor was identified was indicated by responses on a five-point Likert scale. The data was modeled using proportional odds logistic regression and generalized linear modeling and results from non-Bayesian and semi-Bayesian methods were compared. Encouraging the potential successor to stay and taking active steps to pass on the farm were positively associated with successor identification. The potential successors were discouraged to succeed their parents in the family farm business by preferences for urban conveniences over rural challenges and these preferences were associated with a lack of succession planning.